Peningkatan Pengetahuan dan Keterampilan Pedagogik Guru IPA melalui Pendampingan Asesmen Berbasis Kearifan Lokal - Rikardus Feribertus Nikat; Algiranto Algiranto (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Authentic assessment is one part of the 2013 curriculum grading system with an assessment focus on student activity. Based on the results of studies related to problems in learning in schools, there are two main problems. First, the readiness of teachers in the event that they do not yet have minimal competence in making authentic-based assessment instruments. Both grading systems need to integrate the value of local wisdom in evaluating science learning in accordance with national assessment standards. This assistance is a series of preparation of authentic assessment instruments integrated with local wisdom aimed to improve the skills and knowledge of teacher assessment pedagogy. The preparation of authentic assessments in science learning prioritizes the suitability between the assessment model based on local wisdom and the national. The target of the training made Teachers in Merauke district as target partners. This service uses methods in the form of tests, assignments, theories, lectures, and Focus Group Discusion (FGD) with teachers. The results of this pen gabdian make it easier for teachers to evaluate learning authentically. This is evidenced by the increase in the skill and knowledge of teachers in developingan and conducting authentic assessments based on local wisdom.